Role of the alpha(1)- and alpha(2)-adrenoceptors of the paraventricular nucleus on the water and salt intake, renal excretion, and arterial pressure induced by angiotensin II injection into the medial septal area - Camargo, LAD; Saad, W. A. (Elsevier B.V., 2001)
In this study we investigated the influence of cu-adrenergic antagonists injections into the paraventricular nucleus (PVN) of the hypothalamus on the thirst and salt appetite, diuresis, natriuresis, and presser effects of angiotensin II (ANG II) stimulation of medial septal area (MSA). ANG II injection into the MSA induced water and sodium intake, diuresis, natriuresis, and presser responses. The previous injection of prazosin (an alpha (1)-adrenergic antagonist) into the PVN abolished, whereas previous administration of yohimbine (an alpha (2)-adrenergic antagonist) into the PVN increased the water and sodium intake, urinary, natriuretic, and presser responses induced by ANG ii injected into the MSA. Previous injection of a nonselective alpha -adrenergic antagonist, regitin, into the PVN blocked the urinary excretion, and reduced the water and sodium intake, sodium intake, and presser responses induced by ANG II injected into the MSA. The present results suggest that alpha -adrenergic pathways involving the PVN are important for the water and sodium excretion, urine and sodium excretion, and presser responses, induced by angiotensinergic activation of the MSA. (C) 2001 Elsevier B.V.
Keywords: adrenergic antagonists; water intake; sodium intake; diuresis; natriuresis; arterial pressure; medial septal area; paraventricular nucleus